2021
DOI: 10.1002/met.2002
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of non‐catching precipitation measurement instruments: A review

Abstract: Non-catching type gauges are the emerging class of in situ precipitation measurement instruments. For these instruments, rigorous testing and calibration are more challenging than for traditional gauges. Hydrometeors characteristics like particle size, shape, fall velocity and density must be reproduced in a controlled environment to provide the reference precipitation, instead of the equivalent water flow used for catching-type gauges. They are generally calibrated by the manufacturers using internal procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
(99 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, the lack of moving parts and the reduced maintenance required make them especially suitable for use in harsh environments and automatic weather stations, fostering their incremental adoption. The most relevant factors still preventing a widespread diffusion of NCGs are the lack of standardised calibration procedures and correction algorithms to compensate for instrumental and environmental biases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lack of moving parts and the reduced maintenance required make them especially suitable for use in harsh environments and automatic weather stations, fostering their incremental adoption. The most relevant factors still preventing a widespread diffusion of NCGs are the lack of standardised calibration procedures and correction algorithms to compensate for instrumental and environmental biases [1].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the reference disdrometer is subject to wind-induced biases itself, as demonstrated by Něspor et al (2000) for a now outdated version of the 2DVD and by Chinchella et al (2021) for the Thies LPM optical disdrometer. Further insights could be therefore achieved by obtaining bias corrected DSD measurements, a topic which is not addressed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Among various applications, disdrometers can be used to improve the integral measurements of precipitation (cumulated depth and intensity) obtained from traditional gauges. Optical disdrometers (Lanza et al, 2021) are widely used to obtain suitable PSD and fall velocity measurements. The two-dimensional video disdrometer (2DVD), manufactured by the Johanneum Research Institute, demonstrated high performance and is used in various scientific works (see Kruger and Krajewski, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used empirical formulas are shown in Table 3. The empirical formula of raindrop terminal velocity formula proposed by Atlas et al (1973) based on Doppler weather radar data has been widely used (Jiang et al, 2019; Lanza et al, 2021; Liu et al, 2018).…”
Section: Challenges In Video‐based Rainfall Monitoringmentioning
confidence: 99%
“…The commonly used empirical formulas are shown in Table 3. The empirical formula of raindrop terminal velocity formula proposed by Atlas et al (1973) based on Doppler weather radar data has been widely used (Jiang et al, 2019;Lanza et al, 2021;Liu et al, 2018). Similar to weather radar and microwave link rainfall measurements, the terminal velocity assumption is often used in video-based rainfall calculations (Allamano et al, 2015;Jiang et al, 2019;Wang, Wang, Liu, Zhu, et al, 2022).…”
Section: Terminal Velocitymentioning
confidence: 99%